Influence of combined vitamin D3 supplementation and resistance exercise training on musculoskeletal health in older men and women (EXVITD): protocol for a randomised controlled trial - Carolyn A Greig; Neil Gittoes; Janet Lord; Susan Lanham-New; Alison Doyle; Anneka Elizabeth Welford; Julie Robinson (BMJ Open)
Introduction Sarcopenia is a progressive loss in muscle mass, strength and function, the adverse consequences of which are severe, affecting quality of life and placing an increasing burden on social and healthcare systems. Vitamin D status is known to be associated with markers of sarcopenia, namely muscle mass, strength and function. Also, resistance exercise training (RET) is currently the only proven intervention to treat sarcopenia. However, very little data exist on the influence of combining the two interventions of vitamin D supplementation and resistance exercise training, although a recent systematic review provides tentative support for the current study’s hypothesis that the combined intervention may further improve musculoskeletal function above exercise training alone. The aim of the present study is to determine whether vitamin D3 supplementation is any more effective in improving musculoskeletal function when combined with RET compared with exercise training alone in older adults.Methods and analysis This double-blinded randomised placebo-controlled trial will recruit a target of 127 eligible men and women aged ≥65 years living independently or in sheltered housing within the Birmingham area to two groups: (1) 6 months RET and placebo or (2) 6 months RET and 800 IU/d vitamin D3. Measures of muscle power (Nottingham Power Rig), body composition (dual energy X-ray absorptiometry), muscle function (short physical performance battery, timed up and go), falls and fractures as events will be assessed. Assessments will take place at baseline and postintervention, with intermittent monitoring of bone turnover, calcium and vitamin D. The primary outcome will be lower limb extensor power output. Analyses of within-group changes and between-group differences in outcome measures are planned.Ethics and dissemination The EXVITD study has ethical approval granted by the Black Country National Health Service Research Ethics Committee (14/WM/1220). Results of this trial will be submitted for publication in peer-reviewed journals and presented at conferences. The study is being conducted according to the principles of the Declaration of Helsinki.Trial registration numberNCT02467153; Post-results.